Why having a job is not always enough to get out of poverty: Evidence from Turkey - ACET DÖNMEZ, GİZEM; ERİŞ DERELİ, BİLGE (My University, 2023)
Employment is often regarded as a key to getting out of poverty. However, having a job is not always sufficient to escape from being poor. In-work poverty is a prevalent phenomenon in many countries nowadays. This paper seeks possible explanations for working poverty by using the at risk of poverty or social exclusion (AROPE) definition of Eurostat and taking Turkey as a case study. For this purpose, it first measures AROPE among the working population utilizing the Survey of Income and Living Conditions (SILC) for the year 2022 and finds that 21.95 per cent of the working population in Turkey are poor. Considerable heterogeneity in poverty rates is observed between sectors. For instance, while more than 35 per cent of the workers in the construction, electricity, and agriculture sectors are poor, this ratio is less than five per cent in finance and insurance activities. There are also significant differences in poverty risks between regions. Intraclass correlation coefficient (ICC) indicates that 14 per cent of the variation in the probability of being poor or not is explained by regional effects at the NUTS-2 level. Therefore, correlates of in-work poverty are investigated through a multilevel logistic regression analysis where both the individual and regional level characteristics are considered. In these estimations, job sectors are controlled to reveal within-sector effects. Preliminary findings show that public employment, social security registration, and higher years of schooling are associated with a lower probability of working poverty, while household dependency raises this risk. Furthermore, compared to the self-employed, employers are much less likely to be poor, whereas casual employees and regular employees are more vulnerable to poverty. Finally, it is found that while an increase in regional GDP per capita lowers the poverty risk, a rise in regional unemployment rate and Gini exacerbates it.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Kalkınma İktisadı ve İktisadi Büyüme; Social Sciences and Humanities; Economics; Development Economics and Economic Growth; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities